2012
DOI: 10.1124/mol.111.075853
|View full text |Cite
|
Sign up to set email alerts
|

Selective, Direct Activation of High-Conductance, Calcium-Activated Potassium Channels Causes Smooth Muscle Relaxation

Abstract: High-conductance calcium-activated potassium (Maxi-K) channels are present in smooth muscle where they regulate tone. Activation of Maxi-K channels causes smooth muscle hyperpolarization and shortening of action-potential duration, which would limit calcium entry through voltage-dependent calcium channels leading to relaxation. Although Maxi-K channels appear to indirectly mediate the relaxant effects of a number of agents, activators that bind directly to the channel with appropriate potency and pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…For example, the voltage-sensitive oxonol dye and related analogs can activate b1-containing and neuronally abundant, b4-containing BK channels (Morimoto et al, 2007) [4-chloro-7-(trifluoromethyl)-10H-benzofuro[3,2-b]indole-1-carboxylic acid], and the tetrahydroquinoline termed compound Z [(3aR,4S,9bS)-4-(Naphthalen-1-yl)-3a,4,5,9b-tetrahydro-3H-cyclopenta[c]quinoline-8-carboxylic acid] (Lee et al, 2012;Ponte et al, 2012) all induce BK channel activation in absence of BK b1, with drug action being likely mediated by the ubiquitously distributed BK a subunit. It remains unknown whether NS1619 amido derivatives promote relaxation of KClprecontracted isolated thoracic aortic rings via BK b1 subunits (Calderone et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the voltage-sensitive oxonol dye and related analogs can activate b1-containing and neuronally abundant, b4-containing BK channels (Morimoto et al, 2007) [4-chloro-7-(trifluoromethyl)-10H-benzofuro[3,2-b]indole-1-carboxylic acid], and the tetrahydroquinoline termed compound Z [(3aR,4S,9bS)-4-(Naphthalen-1-yl)-3a,4,5,9b-tetrahydro-3H-cyclopenta[c]quinoline-8-carboxylic acid] (Lee et al, 2012;Ponte et al, 2012) all induce BK channel activation in absence of BK b1, with drug action being likely mediated by the ubiquitously distributed BK a subunit. It remains unknown whether NS1619 amido derivatives promote relaxation of KClprecontracted isolated thoracic aortic rings via BK b1 subunits (Calderone et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…. Human mutations that cause asthma and mouse genetic and pharmacological studies suggest that Slo1 activators might provide benefit in the treatment of asthma, hypertension and over-reactive bladder (9)(10)(11)(12)(13)(14)(15). We thus applied LFA to the Slo1 channel to identify molecules that would open the channel.…”
Section: Significancementioning
confidence: 99%
“…The hERG channel is the dangerous off-target of many drugs that, by inadvertently inhibiting hERG, cause drug-induced long QT syndrome with the potential of torsades de pointes and sudden death (8). High-conductance Ca 2+ -activated K + (Slo1) channel of the K Ca subfamily regulates smooth muscle contraction, and activators of the Slo1 channel are drug candidates for asthma, over-reactive bladder, and hypertension (9)(10)(11)(12)(13)(14)(15). These channels are just a small subset of examples illustrating the important roles of K + channels to different physiological functions.…”
mentioning
confidence: 99%
“…More recent studies have identified the bisarylthiourea NS11021 [5-(2-{3-[3,5-bis(trifluoromethyl) phenyl]thioureido}-5-bromophenyl)-1H-1,2,3,4-tetrazole], the oxindole BMS-204352 [(3S)-3-(5-chloro-2-methoxyphenyl)-3-fluoro-6-(trifluoromethyl)-2-indolinone], the natural modulator dihydrosoyasaponin-1 (for review, see Ghatta et al, 2006;Nardi and Olesen, 2008), the GoSlo-SR family of anthraquinone analogs (Roy et al, 2012(Roy et al, , 2014, as well as the tetrahydroquinoline racemate "X" and its two enantiomers "Y" and "Z" (Ponte et al, 2012). Several of these modulators have shown activity in pharmacological studies in ex vivo organ bath studies using bladder strips (Imai et al, 2001;Tanaka et al, 2003;Malysz et al, 2004; Mora and Suarez-Kurtz, 2005; Ponte et al, 2012).…”
Section: Introductionmentioning
confidence: 99%